Becoming the change : leadership behavior strategies for continuous improvement in healthcare - Toussaint, John; Barnas, Kim (McGraw-Hill, 2021)
"Two renowned healthcare transformation experts reveal how you can implement the principles and behaviors that leaders at all levels must embrace in order to create lasting change. Healthcare is on the brink of a quality revolution-one that requires deeply personal as well as organizational changes. In Becoming the Change, two pioneers in the healthcare transformation movement show you how to cultivate principle-driven behaviors that can turn the tantalizing possibilities on the healthcare horizon into reality. Transformational improvement has often been aimed at frontline healthcare workers rather than leaders at all levels, resulting in "islands of excellence" that are unsustainable. Toussaint and Barnas demonstrate how change needs to start at the top-whether you're an executive, a governing board member, a manager, or a physician. Drawing on a wealth of case studies, they explore how change actually happens, and reveal how healthcare systems led by people who are compassionate, principled, and engaged can undergo profound and lasting transformation"--